Global Existence and Blow-Up for a Chemotaxis System - Xueyong Chen; Fuxing Hu; Jianhua Zhang; Jianwei Shen (Mathematical Modelling and Analysis, 2017)
In this paper we consider a Keller-Segel-type chemotaxis model with reaction term under no-flux boundary conditions, where the kinetics term of the system is power function. Assuming some growth conditions, the existence of bounded global strong solution to the parabolic-parabolic system is given. We also give the numerical test and find out that there exists a threshold. When the power frequency greater than the threshold, both global solution and blow-up solution exist.